Survey on the impact of digital marketing on Algerian consumer purchase decisions - Madi, Ilham; Telli, Mossa; Mosbah, Smail (The International tax journal, 2025)
This study examine the impact of digital marketing channels on consumer purchase decisions in aleria with a particular focus on social media platforms and digital advertisements, the research employs a mixed-methods approach, analysing primary survey data from algerian consumers across different demographic segments the finding reveal that while digital marketing has transformed consumer behavior in Algeria, its influence varies across different stages of the purchase decision process with the most significant impact observed during the information search and evaluation of alternatives phases interestingly the correlation between digital marketing exposure that other factors may moderate this relationship gender differences in purchasing contributes to the growing body of literature on digital marketing in emerging markets and provides practical implication for marketers targeting Algerian consumers in an increasingly digitalized marketplace.